A study on microbial self-healing concrete using expanded perlite - Amjad, Usama Bin; Siddique, Muhammad Shahid; Shahid, Taha; Iftikhar, Ahmed; Alogla, Saleh M.; Ahmad, Jawad (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The increasing concern for the safety and sustainability of structures is calling for the development of smart self-healing materials and preventive repair methods. This research is carried out to investigate the extent of self-healing in normal-strength concrete by using Sporosarcina aquimarina – NCCP-2716 immobilized in expanded perlite (EP) as the carrier. The efficacy of crack-healing was also tested using two alternative self-healing techniques, i.e. expanded perlite (EP) concrete and direct introduction of bacteria in concrete. A bacterial solution was embedded in EP and calcium lactate pentahydrate was added as the nutrient. Experiments revealed that specimens containing EP-immobilized bacteria had the most effective crack-healing. After 28 days of healing, the values of completely healed crack widths were up to 0.78 mm, which is higher than the 0.5 mm value for specimens with the direct addition of bacteria. The specimen showed a significant self-healing phenomenon caused by substantial calcite precipitation by bacteria. The induced cracks were observed to be repaired autonomously by the calcite produced by the bacteria without any adverse effect on strength. The results of this research could provide a scientific foundation for the use of expanded perlite as a novel microbe carrier and Sporosarcina aquimarina as a potential microbe in bacteria-based self-healing concrete.